A Lyapunov-Based Model Predictive Control Design With Reduced Sensors for a PUC7 Rectifier - Makhamreh, Hamza; Trabelsi, Mohamed; Kukrer, Osman; Abu-Rub, Haitham (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
This article proposes a Lyapunov-based model predictive control (MPC) design for a dual output multilevel rectifier. The investigated topology, a seven-level packed U-cell (PUC7) converter, is selected based on its high reliability, compactness, and low cost. The proposed controller has the following advantages over the conventional MPC controllers: First, no gain tuning is required; second, easy implementation; and third, reduced number of sensors (the load currents are estimated using the mathematical model of the PUC7 rectifier). Simulation and experimental results are provided to show the high dynamic performance and effectiveness of the Lyapunov-based MPC controller in tracking the output voltage references under grid change and parameters mismatch conditions.
Keywords: Lyapunov function; model predictive control (MPC); multilevel rectifier; packed U-Cell (PUC) converter